2007
DOI: 10.1111/j.1399-6576.2007.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index monitoring: appreciated but does not affect drug dosing and hypnotic levels*

Abstract: Although BIS became considerably appreciated, growing experience and repeated education had no impact on drug dosing and BIS levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Perhaps, this could be due to the inefficient method of monitoring of the concentration of the drug and the analysis of TIVA in these patients compared with the ability to measure the concentration of an inhaled agent (MAC equivalent and end-tidal drug concentration) in patients receiving inhaled agents. [27][28][29][30] In this investigation, some cases were found to be special. These were usually short procedures, and were in medical centers with large surgical volumes.…”
Section: Discussionmentioning
confidence: 70%
“…Perhaps, this could be due to the inefficient method of monitoring of the concentration of the drug and the analysis of TIVA in these patients compared with the ability to measure the concentration of an inhaled agent (MAC equivalent and end-tidal drug concentration) in patients receiving inhaled agents. [27][28][29][30] In this investigation, some cases were found to be special. These were usually short procedures, and were in medical centers with large surgical volumes.…”
Section: Discussionmentioning
confidence: 70%
“…In line with Religa et al , 6 the present study found a relationship between the observations of dentists and BIS readings, with lower BIS readings associated with assessments of deeper sedation. Despite this relationship, Lindholm et al 27 have speculated that less experienced providers of anaesthesia would be more likely to rely on the BIS monitor to judge sedation levels than their more experienced colleagues, and the same may be true for paediatric dentists. Although in some cases it may be difficult to obtain useful BIS data during moderate sedation, dentists should check the BIS monitor to re‐evaluate sedation levels in order to ensure patient safety, even if a patient demonstrates excellent behaviour with no disruption during sedation.…”
Section: Discussionmentioning
confidence: 99%
“…As the transition between responsiveness and unresponsiveness is clinically meaningful, and might provide an approximation of the switch between consciousness and unconsciousness, pEEG devices have also been tested for their ability to detect this transition with a variety of anaesthetic agents . Unfortunately, with all pEEG devices, there is no specific value of the index, or even a relatively narrow range, that reliably predicts when this transition occurs, both within and between individuals . Nonetheless, even if pEEG monitors do not precisely track anaesthetic depth or discriminate consciousness from unconsciousness, it does not mean that they are not useful in broadly guiding anaesthetic management.…”
Section: Does Peeg or Bis Guidance Influence Anaesthetic Management?mentioning
confidence: 99%
“…challenged the notion that pEEG guidance could markedly alter anaesthetic administration. In this study, certified registered nurse anaesthetists (CRNAs) were trained in the use of BIS monitors . Despite increasing experience with the BIS and subjective appreciation of its value, the average doses of anaesthesia administered by them were not altered when they used the BIS nor were there any differences in BIS values when the BIS was applied but they were blinded to the index .…”
Section: Does Peeg or Bis Guidance Influence Anaesthetic Management?mentioning
confidence: 99%